Impact of covid-19 on oral and maxillofacial surgeries at the Hospital de Urgências de Teresina-PI (Research, Society and Development, 2022)
In March 2020, Piauí diagnosed the first cases of covid-19, a new virus for the scientific community, which brought many challenges to the population and health professionals. With this virus, there was a drastic drop in the numbers of elective care as well as in emergency care, the lack of protocols, as well as the absence of adequate protection measures that made it impossible for the calls to continue. In a survey carried out by the Brazilian College of Oral and Maxillofacial Surgery and Traumatology, a drop of 92.5% was detected in terms of scheduled surgeries. This number is a warning about the need to plan and act in order to prevent overcrowding related to postponed procedures. This work aims to analyze how covid-19 influenced and changed the oral maxillary surgical schedules of this emergency hospital, to identify the perception of the professionals involved regarding these changes. The results prove that after a year of the pandemic, some problems still persist: EPI'S in small numbers, professionals reporting fatigue and reduced number of surgeries when compared to before the pandemic.